Upaya Meningkatkan Hasil Belajar Lompat Jauh dengan Menerapkan Pendekatan Saintifik pada Mata Pelajaran PJOK Siswa Kelas VII-A SMP Negeri 11 Mataram - Saing, Muhammad (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine how the application of a scientific approach to improve the activity and learning achievement of class VII.A students of SMP Negeri 11 Mataram in the Long Jump. This type of research is classroom action research (CAR). In this research, cycle data is used, each cycle is carried out according to a scenario that has been created and is designed into four stages, namely: planning, implementing action, observing, and reflecting, this will take place simultaneously, the sequence can be modified. The instruments used in this study were observation sheets and learning outcomes tests. The subjects in this study were students of class VII.A SMP Negeri 11 Mataram, totaling 26 students. The data analysis technique used is the technique of student learning outcomes and student learning activity data. Based on the results of research on observation sheets and learning outcomes tests for students of class VII.A SMP Negeri 11 Mataram, it can be seen that for the first cycle the results of the Skills Test, Attitude Understanding, and Knowledge Test both male and female have not met the criteria for achieving Classical Completeness (KK). standardized 85% of the number of students with a KKM score of 75 While for the second cycle, the results of the Skills Test, Attitude Understanding, Knowledge Test for Men and Women have met the criteria for achieving classical completeness (KKM) with a standard of 85% of the number of students taking the test results belar with a value of 75. These results can be concluded that there is an increase in activity and learning achievement in the Long Jump. Class VII.A students of SMP Negeri 11 Mataram.